Exploring barriers and enabling factors for surgical task sharing with physician assistants in Liberia: a qualitative pre-implementation study - Håkon A Bolkan; Alex J van Duinen; Ankie van den Broek; Theophilus C Hampaye; Markus Jan Werz (BMJ Open)
Objectives This study explores potential barriers and enabling factors that may influence the acceptance of implementation of a surgical task-sharing initiative targeting physician assistants (PAs) in Liberia.Design A qualitative, pre-implementation study using semistructured interviews. Data was analysed in NVivo V.12 using deductive coding and the consolidated framework for implementation research as a guide.Setting Liberia has few surgical providers and a poor surgical infrastructure resulting in a very low surgical volume. The research was conducted in the context of an already running surgical task-sharing programme for midwives.Participants In 2019, a total of 30 key stakeholders in the field of surgery and the PAs training programme were interviewed.Results The majority of the stakeholders supported the idea of training PAs in surgery. The high unemployment rate among PAs and the need for career advancement of this cadre were important enabling factors. Resistance against surgical task sharing for mid-level clinicians is multifaceted. The Ministry of Health (MOH) did not share a common vision. Opponents within the MOH believed budgetary constraints within the MOH and the lack of surgical infrastructure is a more pressing problem compared with the surgically trained human resources. Another important group of opponents are medical officers (MOs) and their professional bodies. Many of their negative beliefs around surgical task sharing reflect lessons to be drawn from the current surgical training programme for midwives.Conclusion Prior to deciding on implementation of a surgical training programme for PAs, wider support is needed. If surgical task sharing with PAs is to be considered, the intervention should focus on adapting the ‘adaptable’ periphery of the intervention to broaden the support of the MOH, MOs and their professional bodies. Failing to obtain such support should make the implementors consider alternative strategies to strengthen surgical human resources in rural Liberia.